Effect of Garlic (Allium Sativum) Extract on Hemoglobin Levels in Chronic Hemodialysis Patients - Ramadhan, Philosophia; Alif Fathur Rachman, Muhammad; Ali, Zulkhair; Effendi, Ian; Novadian, Novadian; Suprapti, Suprapti; Saleh, Irsan (Journal of World Science, 2023)
CKD patients undergoing hemodialysis have increased inflammatory biomarkers. Anemia in CKD is associated with an advanced degree of inflammation while undergoing chronic hemodialysis. Garlic (Allium sativum) has anti-inflammatory and antioxidant effects, which are expected to improve the degree of inflammation in CKD patients. This study aims to assess the effect of garlic extract on hemoglobin levels in patients undergoing chronic hemodialysis. This study was an experimental study with a double-blind, randomized clinical trial design. This study was a crossover, randomized, placebo-controlled, double-blind trial. The study subjects were 40 stages 5 CKD patients undergoing chronic hemodialysis, randomly divided into two groups, namely the group that received 1000 mg of garlic extract per day (2x500 mg) for six weeks and the group that received a placebo, then a 2-week wash-out period. And after that, the two groups were given alternate treatment. Statistical analysis was carried out using the SPSS version 25.0 program. A total of 40 subjects participated in the study, 57.5% male. The mean age of the subjects was 48.6 (26-59) years. The results showed that there was a significant difference in Hb levels in the garlic group (p = 0.047), where the increase in Hb was from 10.2 (9.2–11.8) mg/dl to 10.23 (8.9–11.6) mg/dl while in the placebo group, there was a decrease in Hb from 10.18 (9.6 – 11.2) mg/dl to 10.05 ± 0.52 mg/dl. Garlic extract can reduce levels of inflammation which can then increase hemoglobin levels.